STUDI KESESUAIAN DAN DAYA DUKUNG KAWASAN UNTUK REKREASI PANTAI DI PANTAI PANJANG KOTA BENGKULU - Nugraha, Himavan Prathista; Indarjo, Agus; Helmi, Muhammad (977-2407769)
resort in the Panjang Beach area. One form of the beach tourism is the beach recreation activities. However, in its efforts to the development of tourism in Panjang Beach needed to be identified and approaches the problems first. The most fundamental and the goal of this research is to conduct a study on the level of suitability and carrying capacity of the Panjang Beach coast primarily for recreational activities. Research carried out by field observations (collecting primary data and secondary data) for 2 months in July 2012 until August 2012 at the Panjang Beach city of Bengkulu, which is divided into seven-point sampling locations from the south up to the north shore. Collecting primary data consist of physics and chemistry sea water data and suitability parameters of beach recreation, such as type of beach, width of the beach, slope of the beach, brightness of sea water, current velocity, water depth, water base material, beach land cover, presence of harmful organism and availability of fresh water. The method used to analyze the results of the research is descriptive method with the help of Tourism Suitability Index analysis and the carrying capacity of Regions that generate value and suitability of the tourist carrying capacity. Based on the results obtained from the calculation of tourism suitability index for coastal recreation activities are mostly above 80%. This indicates that the coastal areas of Bengkulu City, Panjang Beach classified in the category of Highly Suitable (S1) for coastal recreation activities. While the value Capability Area of the Panjang Beach approximately 42.045 people per day.